Prawnie istotne aspekty interpretacji językoznawczej – przykład 2: zakres znaczeniowy leksemu zboczeniec (i czy jest nim homoseksualista?) - Szczyszek, Michał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
In the article, I discuss the legal aspects of language: using linguistic analyses for the benefit of the courts. I discuss linguists’ court communication situation and the expectations towards them. The starting point is one exemplary court case in which an expert linguist was appointed to issue an opinion on the evidence. The conclusions fall into two categories: linguistics and forensic science. Linguistic conclusions, developed in accordance with traditional methods of lexicographic analysis and lexicological and semantic analysis, are not necessarily (because they would not have to be) innovative for linguists. It was more important to show the situation of a linguist in court, the structure of judicial opinion and the procedures for building the linguistic response to a process inquiry as seen from the forensic perspective.